Examining the relationship between health-related behaviors and subjective well being among college students - Levy, Nicolle E., author; Rickard, Kathy, advisor; Rosén, Lee, committee member; Kennedy, Cathy, committee member; Cropanzano, Russell, committee member (Colorado State University. Libraries, 2002)
This exploratory study examined the relationship between health-related behaviors and subjective well being (SWB). SWB refers to the subjective evaluation of one's life satisfaction and affective experiences. The association between health-related behaviors and subjective physical health was also explored. Students' readiness to change was also assessed. The data was separated into three categories: health promoting behaviors (e.g. healthy eating, exercise, sleep, social support, responsible drinking, and condom use), health compromising behaviors (e.g. drinking and driving, fighting, safety, sexual abuse, and alcohol, marijuana and cigarette use), and psychological variables (e.g. depression and perception of weight). SWB was measured with the Satisfaction With Life Scale (Diener et al., 1983) and the Index of Psychological Well-Being (Berkman, 1971). The results revealed that several health promoting, health compromising, and psychological variables were related to emotional well being, satisfaction with life, and subjective health. Although, only a few of the individual variables were predictive in nature, the categories of health promoting behaviors and the psychological variables were found to be predictive of SWB, while behaviors in all three categories were predictive of physical health. Furthermore, it was found that most students were not highly motivated to change their current set of health behaviors. Based on these findings, potential treatment and intervention strategies are then discussed.
Keywords: psychotherapy; clinical psychology